2016
DOI: 10.5194/se-7-301-2016
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of inorganic phosphorus in profiles and particle fractions of Anthrosols across an established riparian buffer and adjacent cropped area at the Dian lake (China)

Abstract: Abstract. Riparian buffers can trap sediment and nutrients sourced from upper cropland, minimizing the eutrophication risk of water quality. This study aimed to investigate the distributions of soil inorganic phosphorus (Pi) forms among profile and particle-size fractions in an established riparian buffer and adjacent cropped area at the Dian lake, southwestern China. The Ca-bound fraction (62 %) was the major proportion of the Pi in the riparian soils. After 3 years' restoration, buffer rehabilitation from cr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…This study found that the average amount of TP (0–10 cm) in the Nitisols and Gleysols was up to 1.1 g/kg (Table ), which is several‐fold greater than that reported for the average topsoil TP level in the tropical and subtropical region of China (Zhang et al ., ). Our results also showed that the greatest portion of P was present in the calcium‐bound Pi fraction both of Nitisols and Gleysols in the region, which suggested that some of the soil's alluvial parent material probably originated from the limestone bedrock in the area above the catchment (Zhang & Li, ). Compared with Gleysols, Nitisols had greater amounts of calcium‐bound Pi on both an absolute and relative basis and smaller Po fractions on a relative basis.…”
Section: Discussionmentioning
confidence: 52%
“…This study found that the average amount of TP (0–10 cm) in the Nitisols and Gleysols was up to 1.1 g/kg (Table ), which is several‐fold greater than that reported for the average topsoil TP level in the tropical and subtropical region of China (Zhang et al ., ). Our results also showed that the greatest portion of P was present in the calcium‐bound Pi fraction both of Nitisols and Gleysols in the region, which suggested that some of the soil's alluvial parent material probably originated from the limestone bedrock in the area above the catchment (Zhang & Li, ). Compared with Gleysols, Nitisols had greater amounts of calcium‐bound Pi on both an absolute and relative basis and smaller Po fractions on a relative basis.…”
Section: Discussionmentioning
confidence: 52%